EVALUATION OF THE EFFECTIVENESS AND SAFETY OF THE I-GEL SUPRAGLOTTIC AIRWAY IN ANESTHESIA FOR REGIONAL LIPOSUCTION PROCEDURES AT GANGWHOO AESTHETIC HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Background: Regional liposuction procedures have become increasingly common in aesthetic surgery. The selection of an appropriate airway management strategy plays a crucial role in ensuring effective ventilation, hemodynamic stability, and minimizing anesthesia-related complications. The i-gel supraglottic airway is a newer-generation device that has been widely adopted in clinical practice; however, data evaluating its effectiveness and safety in liposuction surgery in Vietnam remain limited.Objective: To evaluate the effectiveness and safety of anesthesia using the i-gel supraglottic airway in regional liposuction procedures at Gangwhoo Aesthetic Hospital.Methods: A prospective cross-sectional descriptive study was conducted on 72 patients aged 18 years and older who underwent general anesthesia with the i-gel supraglottic airway for regional liposuction at Gangwhoo Aesthetic Hospital between May 2025 and July 2025. Outcome measures included patient characteristics, success rate of i-gel insertion, airway pressures, gas exchange parameters, hemodynamic variables, and airway-related adverse events.Results: The first-attempt success rate of i-gel insertion was 98.6%, with no cases requiring conversion to endotracheal intubation. The mean peak airway pressure was 14.24 ± 1.87 cmH₂O, and the mean oropharyngeal leak pressure was 26.8 ± 3.9 cmH₂O. Oxygen saturation (SpO₂) and end-tidal carbon dioxide (EtCO₂) were maintained within physiological ranges throughout anesthesia. No episodes of regurgitation, aspiration, postoperative sore throat, or hoarseness were recorded.Conclusions: The i-gel supraglottic airway is an effective and safe airway management device for general anesthesia in regional liposuction procedures and is suitable for routine use in aesthetic surgery settings.
Keywords: i-gel supraglottic airway; liposuction; general anesthesia; airway safety.